Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1002/jms.725
|View full text |Cite
|
Sign up to set email alerts
|

Identification, quantification and comparison of major non‐polar lipids in normal and dry eye tear lipidomes by electrospray tandem mass spectrometry

Abstract: Millions of individuals suffer from a health condition known as keratoconjunctivitis sicca (KCS, also known as 'dry eye'). Studies have indicated that the lipids in the tear film layer, which covers the outer portion of the eye, may be directly correlated with the existence of dry eye syndrome. By identifying and comparing the major, non-polar lipids in normal eye tears with a dry eye model, it may be possible to identify a symptom of, or a contributing factor to, dry eye. Electrospray tandem mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 58 publications
4
34
1
Order By: Relevance
“…This class of compounds corresponded to an earlier preliminary observation stating that human tears contain a new range of compounds with higher polarity than the nonpolar components of meibum that coelute with authentic DAGs ( 13 ). On the other hand, Ham et al ( 31 ) had also previously reported the presence of a few DAG species, such as DAG16:0/16:0 and DAG 16:0/18:0, in the human tears.…”
Section: Analytical Workfl Ow Facilitated Characterization Of Polar Lsupporting
confidence: 85%
“…This class of compounds corresponded to an earlier preliminary observation stating that human tears contain a new range of compounds with higher polarity than the nonpolar components of meibum that coelute with authentic DAGs ( 13 ). On the other hand, Ham et al ( 31 ) had also previously reported the presence of a few DAG species, such as DAG16:0/16:0 and DAG 16:0/18:0, in the human tears.…”
Section: Analytical Workfl Ow Facilitated Characterization Of Polar Lsupporting
confidence: 85%
“…[cc ϩ H] ions are generated with the shift of H from the hydroxy or hydroperoxy to the ␥ position in segment cc through a ␤-ene rearrangement if the segment cc has a ␤ double bond, an ␣ vinyl single bond, and an allylic hydrogen (for 20-HDHA and 17-HDHA) or conjugatedtriene (for 17 cc in RvD1 and PD1, 12 cc of LTB 4 [19], 15 cc of LXA 4 [19] that can facilitate the migration of electrons from the ␤ double bond to the ␥-bond and convert the ␣ vinyl single bond to an ␣ allylic single bond. Examples are ions m/z 277 from RvD1 ( Figure 1 and Scheme 3), 261 from PD1 ( Figure 2, Scheme 4), 245 from 17-HpDHA (Figure 4 and Scheme 6), 195 from LTB 4 and 251 from LXA 4 [27,29], as well as ions 285 from 20-HDHA, 245 from 17-HDHA, 205 from 14-HDHA, and 165 from 11-HDHA (Table 1, Supplemental Figure 1 and Scheme 5).…”
Section: [Cc ϩ H] Ions In Ms/ms Of Lipid Mediatorsmentioning
confidence: 99%
“…They also developed an analytical method and conducted stereochemistry studies of all the HDHAs produced by human platelets and rat brain homogenates using chiral LC-thermospray-MS and GC/MS (electron-impact ionization) [11]. Low-energy ionization primarily generates molecular (or pseudo-molecular) ions for collision-induced dissociation (CID) MS/MS analysis, through which the MS/MS spectra obtained are used widely to identify and elucidate the structures of lipid mediators derived from polyunsaturated fatty acids [12][13][14][15][16][17][18][19][20]. The lowenergy CID of eicosanoids includes charge-remote and charge-directed fragmentations [12,21], many of which occur through "␣-hydroxy-␤-ene like rearrangement" as referred to by Murphy, i.e., ␣-cleavage of the carbonOcarbon bond (␣ position to hydroxy group), facilitated by a double bond (ene) in the ␤ position [22].…”
mentioning
confidence: 99%
“…The lipid composition of TFLL is critical for maintaining the stability of the preocular tear film, deterioration of which has been associated with various ocular diseases and pathological conditions. Human meibum has been shown to have a large number of diverse lipid species, including wax esters (WE) (3, 5-7, 12, 16-20, 25, 26), cholesteryl esters (Chl-E) (3,5,7,11,12,18,20,25,26), mono-, di-, and triacyl glycerols (3, 5-7, 14, 16-18, 20, 21, 25, 26), hydrocarbons (6), free fatty acids (31), sterols (1, 3-7, 9, 11-13, 16-20), phospholipids (2,6,7,15,19,21,22,25,26), ceramides (6,21), and many other poorly identified lipid compounds. Historically, the main methods used to characterize meibomian lipids were TLC (3-5, 15, 20-22), gas-liquid chromatography (6-10, 13), and gas chromatography-electron ionization GC-MS (11, 15, 20-22, 30, 31), HPLC with UV detection (15,(20)(21)(22), infrared spectrometry (27,28), and, more recently, various types of modern mass spectrometry (MS) techniques with or without HPLC (16,17,19,23,25,26).…”
mentioning
confidence: 99%